QTL analysis for early yield in a pseudo F2 population of cassava - Okogbenin, Emmanuel; Marín, J.; Fregene, Martin A. (2008)
Genetic mapping of early bulking in a full-sib population of cassava was continued in a selfed family of 268 cassava plants derived from a single progeny of the full-sib population. The pseudo F2 population was analysed with 122 segregating SSR markers. A previously constructed linkage map of cassava consisting of 22 linkage groups covering 1236.7 cM, with an average marker distance of 18 cM was used for this study. The F2 population was evaluated for components of early yield, namely dry root yield (DR) at 7 months, harvest index (HI), and weight of fresh foliage (FF). Interval mapping, with single- and two-QTL models, was used to identify QTLs. The single-QTL model identified three QTLs each for DR, FF, and HI. The two-QTL model approach identified groups of QTLs that together explained 33% for FF, 43.5% for DR and 36% for HI. The identification of QTLs involved in early yield is an important step toward understanding quantitative genetic variation of early yield and implies reconsideration of breeding strategies for improvement of this complex trait.